Screening potential biomarkers of cholangiocarcinoma based on gene chip meta-analysis and small-sample experimental research - Shen, Hengyan; Bai, Xinyu; Liu, Jie; Liu, Ping; Zhang, Tao (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) is a rare malignant tumor with a poor prognosis. This study aimed to identify CCA biomarkers by investigating differentially expressed genes (DEGs) from CCA patients and healthy subjects obtained from the Gene Expression Omnibus database. Bioinformatics tools, including the Illumina BaseSpace Correlation Engine (BSCE) and Gene Expression Profiling Interactive Analysis (GEPIA), were used. The initial DEGs from GSE26566, GSE31370, and GSE77984 were analyzed using GEO2R and VENN, and protein-protein interaction networks were constructed using STRING. The BSCE was applied to assess curated CCA studies to select additional DEGs and compare DEGs across the 10 biosets, which was supported by findings in the literature. The final 18 DEGs with clinical significance for CCA were further verified using GEPIA. These include CEACAM6, EPCAM, LAMC2, MMP11, KRT7, KRT17, KRT19, SFN, and SOX9, which were upregulated, and ADH1A, ALDOB, AOX1, CTH, FGA, FGB, FGG, GSTA1, and OTC, which were downregulated in CCA patients. Among these 18 genes, 56 groups of genes (two in each group) were significantly related, and none were independently and differentially expressed. The hub genes FGA, OTC, CTH, and MMP11, which were most correlated with the 18 DEGs, were screened using STRING. The significantly low expression of FGA, OTC, and CTH and the significantly high expression of MMP11 were verified by immunohistochemical analysis. Overall, four CCA biomarkers were identified that may regulate the occurrence and development of the disease and affect the survival rate of patients with CCA, and they have the potential to become diagnostic and therapeutic targets for patients with CCA.